AHM Journal 2020
DOI: 10.30756/ahmj.2020.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Music Medicine as a Component of Acute Migraine Attack Management in The Emergency Room: A Randomized Controlled Open-Label Trial

Abstract: Background: Acute severe migraine requiring Emergency Room (ER) visit is managed by giving analgesics for pain relief. Since music medicine has been beneficial in other pain syndromes, the study of its effect as a noninvasive add-on to current management is worth pursuing. Objective: To identify if music medicine in addition to medical therapy will reduce the severity and duration of an acute attack of moderate to severe migraine compared to medical management alone. Methods: An open label randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The brain itself releases neurotransmitters as an answer to music which stimulates the release of endorphins, these modulate pain and as an effect is reflected a feeling of euphoria. In conclusion, listening to music by inhibiting pain and stimulating the release of endorphins, the patient's migraine improves 15 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The brain itself releases neurotransmitters as an answer to music which stimulates the release of endorphins, these modulate pain and as an effect is reflected a feeling of euphoria. In conclusion, listening to music by inhibiting pain and stimulating the release of endorphins, the patient's migraine improves 15 .…”
Section: Introductionmentioning
confidence: 93%
“…There are some studies that suggest that music therapy may help alleviate pain such as cancer pain 13 , procedural pain 14 and it may have a great effect in reducing the severity and duration of an acute migraine attack 15 . It has been reported that adding music to the pharmacological treatment helps decrease the pain severity, as pain impulses travel from the site of injury to the brain throughout the spinal cord in which neural gates indicate the level of pain that is allowed to pass or not to pass.…”
Section: Introductionmentioning
confidence: 99%